2015
DOI: 10.1007/s00535-015-1063-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and diagnostic performance of Wisteria floribunda agglutinin positive Mac-2-binding protein as a preoperative serum marker of liver fibrosis in hepatocellular carcinoma

Abstract: Serum WFA(+)-M2BP levels reflected both the pathological and functional progression of liver fibrosis comprehensively and continuously. Elevated WFA(+)-M2BP levels were a significant risk factor for tumor recurrence and decreased overall survival after liver surgery independent of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 26 publications
4
67
2
Order By: Relevance
“…[1014] Although the diagnostic accuracy of WFA + -M2BP for liver fibrosis has not yet been validated outside Japan, previous Japanese studies demonstrated that it is useful for grading liver fibrosis and can be a useful predictor associated with clinical outcomes. [1014,32,33] Thus, in the near future, this novel liver fibrosis biomarker should attract much attention in Western countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1014] Although the diagnostic accuracy of WFA + -M2BP for liver fibrosis has not yet been validated outside Japan, previous Japanese studies demonstrated that it is useful for grading liver fibrosis and can be a useful predictor associated with clinical outcomes. [1014,32,33] Thus, in the near future, this novel liver fibrosis biomarker should attract much attention in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…WFA + -M2BP is characterized by a fibrosis-related glycoalteration, and test results can be rapidly obtained with a bedside method. [1014] …”
Section: Introductionmentioning
confidence: 99%
“…Thus, its cross-reactive potential severely limits its use for cancer biomarker detection. WFA is currently considered the most prominent diagnostic lectin against cholangiocarcinoma when compared with other homologous lectins (26,35) and the most discriminatory against altered N-glycans on Mac2-binding protein, a secretory N-glycoprotein with elevated expression levels during viral hepatitis induced liver cirrhosis (36,37).…”
mentioning
confidence: 99%
“…We recommend the use of platelet counts rather than serum WFA(+)-M2BP levels in the prediction of liver fibrosis in NASH, PBC, and AIH patients (Figure 1). Previous studies [12,13,14,15,16] have tried to show the effectiveness of this novel non-invasive biomarker for the diagnosis and evaluation of fibrosis and inflammation in various chronic liver diseases. In chronic hepatitis C patients, several studies have reported the effectiveness of several non-invasive biomarkers such as platelet levels, ferritin, and hyaluronic acid [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Kuno et al reported that a rapid and simple glycan-based immunoassay for WFA(+)-M2BP can quantify fibrosis [14]. There are many reports that support the quality of WFA(+)-M2BP in the assessment of fibrosis in HCV patients [15] and PBC patients [16]. Further study may be needed to validate the diagnostic utility of WFA(+)-M2BP in the diagnosis of fibrosis in the full range of chronic hepatitis patients.…”
Section: Introductionmentioning
confidence: 99%